A Modern Protagonist: Keloglan - Ozcan, Tarik (Ahmet Yesevi Univ, 2013)
The understandings of the mythological age and historical age were significantly different from each other, and so were their literary texts. This difference can also be observed in the problem-solving methods of the heroes of the texts belonging to the mythological age and the modern age. This observable tranformation from tradition to innovation is a result of the socio-economical and socio-cultural changes in human life. In this regard, the new establishes its own tradition by attacking the world of the former traditional text and by demolishing its understanding of the human being and of language. Although Keloglan narratives belong to the genre of the fairy tale, the hero's attitude in the face of events, his problem-solving methods and the language he uses signal the understandings of modernity. By criticizing the routine and worn-out world of the epic through the method of reflection, Keloglan has developed a pattern of behaviour close to the logical one of the modern human being. In this study, we have tried to focus on the reasons and results of this transformation in Keloglan's personality.
Keywords: Mythological age; hero image; noble text; modern age; Keloglan